A Contingency Theory of Organization Re-Examined in the Context of a Developing Country - Negandhi, Anant R.; Reimann, Bernard C. (Academy of Management Journal, 1972)
The ?Contingency Theory? of organizations holds that the ?optimum? organization structure is primarily dependent on the external environment of the enterprise. Stable environmental conditions call for centralized structures, while a dynamic environment requires a decentralized structure. This study suggests that a slightly modified version of this ?Contingency Theory? is appropriate in the context of a developing country; namely, India.